PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA DAN KEPUASAN KERJA DENGAN GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL SEBAGAI VARIABEL PEMODERASIANNYA (Studi pada SKPD Provinsi Yogyakarta) - Husni Mubarak (Politeknik Negeri Bengkalis, 2015)
Abstract: This research investigated the model of budgetary participation to leadership styles. This model which is more focused in examination of previous research on job performance and job satisfaction with transactional and transformational variables as moderating variables is based on research by Adler and Reid (2008). SEM techniques used to collect data from questionnaires in the SKPD of the Yogyakarta Provincial Government, Indonesia. This research finds to explain that the behavior of executing the budget on transactional variables has a interaction which (between leader and follower) is a synergy making job relationship. The transformational variables in this research find the interaction which leader and follower are not in line in the job process and the results indicated the possibility of worsening on the job. This research purposed to meet that it is can contribute positively to the concept and build harmony between behavior, budget participation, and leadership style in budget participation. Keyword: transactional leadership, transformational leadership, budget participation, job performance and job satisfaction.